ENDOCRINOPATHIES AND SLEEP APNEA - Bahriyeva , Nigora Naimovna; Mahmudova , Intizor Abdurauf qizi; Keldiyorova , Navbahor Nuriddin qizi; Nazarov, Qilichbek Ilxom o‘g‘li (Educational Research in Universal Sciences, 2024)
One of the most common sleep breathing disorders is obstructive sleep apnea (OSA). It is characterized by recurrent episodes of upper airway collapse during sleep, which lead to severe consequences including intermittent hypoxia, fluctuations in blood pressure and heart rate, increased sympathetic nervous system activity, endocrine dysfunction, and sleep fragmentation1-5.